Ultrasound‐guided micropercutaneous nephrolithotomy in pediatric patients with kidney stones. (14th May 2015) - Bodakçi, Mehmet Nuri; Penbegul, Necmettin; Dağgülli, Mansur; Dede, Onur; Utangaç, Mehmet Mazhar; Hatipoglu, Namık Kemal; Sancaktutar, Ahmet Ali
<x xml:space="preserve">Abstract</x> Objective To present the outcomes of ultrasound‐guided micropercutaneous nephrolithotomy for the treatment of renal stones in pediatric patients. Methods Ultrasound‐guided micropercutaneous nephrolithotomy was carried out on 25 pediatric patients from June 2012 to October 2014. Micropercutaneous nephrolithotomy surgery was completed without the use of fluoroscopy in 19 patients. Medical records were retrieved from our institutional database and retrospectively reviewed. Percutaneous puncture was carried out by an "all‐seeing needle" in seven patients and by a 14‐G intravenous cannula in 18 patients. After entering to the collecting system through an "all‐seeing needle" or by Microsheath, the calculus was fragmented using a 273‐micron holmium yttrium aluminium garnet laser. After the stone was fragmented to the smallest pieces possible, the operation was terminated. Results Single access was obtained in all patients using ultrasound guidance. The average age of the patients was 4.12 ± 5.33 years. The mean stone size was 13.45 ± 3.11 mm. The mean operative time was 51.45 ± 30.69 min. The mean duration of hospitalization was 3.18 ± 1.77 days. Treatment success was 92%. Two patients had residual fragments after the procedure; these patients were followed conservatively. A total of three minor complications were observed and all of them were managed conservatively. Conclusions To our knowledge, this is the first study of ultrasound‐guided micropercutaneous nephrolithotomy in the pediatric population. Our findings suggest that micropercutaneous nephrolithotomy can be safely carried out with ultrasound guidance in children by experienced hands, allowing to minimize risks associated with radiation exposure in this patient population.